Analisis Break Even Point Sebagai Alat Perencanaan Laba pada Konveksi Zein Store - Nur Paujiah, Andini; Isyanto, Puji (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
The purpose of this research is to determine and analyze the Zein Store Konveksi's profit plan by calculating the break-even point. In planning profits, entrepreneurs must pay attention to profits and costs to achieve the desired profit goals. Break Even Point (BEP) can help in evaluating the financial management of Zein Store convection, to ensure that the business can reach the point when revenue equals total costs (fixed costs and variable costs), so it does not experience losses. The method used is descriptive with a quantitative strategy. Data was obtained directly through interviews with the owner of Konveksi Zein Store. The analysis tool used is Break even point. The research results show that Konveksi Zein Store has succeeded in reaching the break-even point and even managed to obtain high profits. After carrying out the analysis, the Zein Store Convection break-even point (BEP) method is suitable as a profit planning tool to find out at which sales the break-even point will be achieved.